Compendium of Evaluation Studies Conducted by Programme Evaluation Organisation (1971-83) Volume - II - Planning Commission (Planning Commission, 1998)
The Community Listening by Radio, introduced in 1939, was made a plan scheme in 1954 with a provision of Central subsidy equal to 50% of the initial cost of the radio set. The objectives of the scheme were to propogate the plan programmes, especially the community projects and to extend basic and social education. The grant of 'Central Subsidy' was subject to the conditions that the sets should conform to the ISI specifications, that the sets should be pretuned to AIR Stations in each region, that not less than 25% of the cost of the set should be recovered from the beneficiaries, that the sets should be maintained well by the States, etc.
Programme Evaluation Organization